Medical profession and practices of intentionally ending a life from Islamic perspective - U Tun Aung, Maulana Akbar Shah (2016)
Life and death of men is in the discretion of Allah, SWT, no one can decide how long they should live, but it is Allah, SWT. However, today in our society life is being terminated by someone, like Doctor or the family of the patients, who are terminally ill and their recovery is absolutely irretrievable according to the medical experts as medication does not show any reaction. In medical science, ending life for such situation is called euthanasia, an act or practice of painlessly putting to death persons suffering from painful and incurable disease or incapacitating physical disorder or allowing them to die by withholding treatment or withdrawing artificial life-support measures. Justification given by pro-Euthanasia is that it is right of the patient who should not suffer unstoppable pain physically and who does not like a burden of medication on their family. They insisted mercy killing is absolutely appropriate if patient’s body is in gradual decline, their organs are in continuous failure, their agonizing pain is unbearable and the cost of their artificial support system is beyond their limit. This issue has been controversial to many Islamic as well as social organizations as it is against their doctrine and norms. Since life and Death is in Allah’ hand, who is to decide that a life has to be ended at so and so time. Is it against predestination and fixation of life by Allah that when the time come no one can stop its arrival. This undesirable situation is confronted by many Muslims in our world too, then is there any room in Sahr’ia law that allows a Physician to end the life of a patient? The objective of this paper is to explore any possibility in Shar’ia law that authenticates ending a life.